Feasibility Study of 10 MW Photovoltaic Power Plant in West Nusa Tenggara, Indonesia - Zurhalki, Muhammad (AMPLITUDO : Journal of Science and Technology Innovation, 2023)
This study aims to provide an overview of renewable energy sources' potential development as a solution to meeting electricity needs in the West Nusa Tenggara, Indonesia by analyzing the feasibility of 10 MW Photovoltaic power plant. The performance simulations and calculations based on renewable energy manufacturing data with RETScreen International software. The findings show that West Nusa Tenggara has good potential for Photovoltaic power plant development. It also indicates the feasibility of renewable energy investment in this region.